2019
DOI: 10.1177/0162643418822070
|View full text |Cite
|
Sign up to set email alerts
|

Video Self-Modeling to Treat Aggression in Students Significantly Impacted by Autism Spectrum Disorder

Abstract: Research suggests that individuals with autism spectrum disorder (ASD) are at risk of exhibiting aggressive behaviors due to deficits in social communication and restricted and repetitive interests. Individuals with greater symptom severity and/or low cognitive abilities are at the greatest risk of developing aggressive behaviors that tend to be resistant to treatment. Additional research to treat persistently high rates of aggressive behaviors in this population is needed. Video self-modeling (VSM) is an evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…ASD has been studied over the last six decades, as reflected in the results obtained. In the analysis of autism in the educational field, it can be seen how students can present problems in various capacities [ 2 , 3 , 4 , 5 , 9 , 10 , 11 ], as well as others that are an advantage [ 18 , 19 ] with respect to other people of typical development. In addition, special attention is paid to the use of technological resources to facilitate the satisfaction of these needs in order to achieve inclusion in learning spaces and society.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ASD has been studied over the last six decades, as reflected in the results obtained. In the analysis of autism in the educational field, it can be seen how students can present problems in various capacities [ 2 , 3 , 4 , 5 , 9 , 10 , 11 ], as well as others that are an advantage [ 18 , 19 ] with respect to other people of typical development. In addition, special attention is paid to the use of technological resources to facilitate the satisfaction of these needs in order to achieve inclusion in learning spaces and society.…”
Section: Discussionmentioning
confidence: 99%
“…Another of the more superficial and concurrent symptoms that they can present is anxiety, which is currently being investigated [ 8 ]. All of this can increase exponentially if the person has a low cognitive ability [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although research has evaluated VM to teach safety skills to children, no study has evaluated VSM to teach safety skills even though it has been shown to be effective in teaching other skills (e.g., Cihak & Schrader, 2008; Kurnaz & Yanardag, 2018; Lee et al., 2007; Sadler, 2019). Cihak and Schrader (2008) compared VM to VSM to teach two vocational tasks to four adults with intellectual disabilities.…”
Section: Evaluation Of Video‐self Modeling To Teach Firearm Safety Sk...mentioning
confidence: 99%
“…They may also present depression, aggressiveness, challenging actions, emotional problems [ 4 , 5 , 6 , 7 ]. In this symptomatological line, there are also people with high levels of anxiety, which is aggravated if the person has a low cognitive level [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%